Dominica : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Dominica. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that the Dominican economy was hit hard by tropical storm Erika in 2015. Agricultural output and manufacturing declined sharply, as the storm affected crops and access to arable land, and prompted the closure of operations of the main industrial plant. Inflation has remained subdued, mainly as a result of falling fuel prices. Notwithstanding weak exports of agriculture and tourism, the 2015 current account deficit remained contained on the back of lower oil imports. Output growth is expected to remain subdued in 2016 at 1.3 percent as the economy slowly recovers from the storm and investment in reconstruction picks up.